2016
DOI: 10.1111/ajd.12491
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity in paediatric psoriasis and its impact on disease severity and progression

Abstract: Although it is not associated with disease severity and course, increased bodyweight may be a health problem for psoriatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The slight female preponderance (1.44:1) was consistent with results of other studies from Turkey and other regions . Nail involvement was associated with arthritis, which other authors have also described . Scalp involvement was more frequent in girls than boys, as has been previously reported and attributed to koebnerization …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The slight female preponderance (1.44:1) was consistent with results of other studies from Turkey and other regions . Nail involvement was associated with arthritis, which other authors have also described . Scalp involvement was more frequent in girls than boys, as has been previously reported and attributed to koebnerization …”
Section: Discussionsupporting
confidence: 91%
“…[33][34][35][36][37] Nail involvement was associated with arthritis, which other authors have also described. 31,37 Scalp involvement was more frequent in girls than boys, as has been previously reported and attributed to koebnerization. 34 Twenty-seven percent of patients were categorized as overweight or obese, which is similar to that reported in another Turkish study focusing on pediatric psoriasis (28%).…”
Section: Emotions Was the Most Severely Impaired Domain Of Caregiversupporting
confidence: 72%
See 1 more Smart Citation
“…Previous studies on children and adolescents with psoriasis have found some of these comorbidities, or risk factors thereof, to be increased 11 23–26. Since these studies have mainly been done in highly selected hospital-treated populations, with small sample sizes, or by retrospectively reviewing, for example, patient records, we wished to investigate paediatric psoriasis in a more general population, and also to include psoriasis-free controls for comparison, with the possibility of prospective data collection 11 23–49. We therefore established a well-characterised clinical cohort nested in a large, nationwide birth cohort in Denmark in order to investigate the clinical characteristics, trigger factors, comorbidities and related risk factors and genotype of paediatric psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Both adults and children with psoriasis are at risk for comorbidities, including obesity, hypertension, hyperlipidaemia, diabetes mellitus, metabolic syndrome, non-alcoholic fatty liver disease (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Since obesity is a known risk factor for most of these comorbidities, it would be useful to determine whether psoriasis is an independent risk factor for some or all of them (6).…”
mentioning
confidence: 99%